To what extent has U.S. foreign policy contributed to an increase in religious inspired terrorism since 1945?. (1st December 2019) - Morris, Charlotte
Abstract : This paper will analyze the role that U.S. Foreign Policy has had on increasing religious inspired terrorism since 1945. Justifications for the War on Terror after 9/11 were for freedom, democracy, and the eradication of terrorism, yet the interventions that have taken place both in the 20th and 21st centuries have neither spread democracy nor freedom and have even increased terrorism, especially in the Middle East and also internationally. The role that each presidential administration after World War II has played in increasing U.S. power and influence in the Middle East has further increased security threats both towards those in the region and Western states. The significant shift in policy after the attacks of 11 September 2001 allowed for the securitization of religious terrorism and a state of exception in which the United States has broken international law and violated human rights through extraordinary measures. The use of drones, in particular by the Obama administration has allowed the War on Terror to move into the shadows from the overt military interventions of George W. Bush in Afghanistan and Iraq, whilst still having a devastating effect on civilians and the stability of the states it targets. The human rights abuses of the United States both in the Middle East and in Guantanamo Bay Naval Base question the legitimacy of the invasions and aims of the democratic state by breaking the rule of law and have also contributed to the increase in religious inspired terrorism.